Indolent Systemic Mastocytosis Manifesting as Protracted Anaphylactic Shock - Chatterjee, Manidipam (Indian J Crit Care Med, 2018)
Systemic mastocytosis is a rare disease due to abnormal proliferation of mast cells (MCs). A case of indolent systemic mastocytosis is presented here. After anesthetic induction for elective thyroid swelling with propofol and atracurium followed by endotracheal intubation, a 57-year-old female patient developed acute hypotension, sinus tachycardia, red rashes, increased airway pressure along with difficult ventilation, and desaturation. She developed multiorgan failure subsequently. MC tryptase level was persistently high. Bone marrow study revealed mastocytosis. She required antihistaminic, steroid, and organ support. With treatment, organ functions recovered gradually. Atracurium precipitated anaphylactic shock causing severe morbidity in this patient.